Novel mutations in BMP1 result in a patient with autosomal recessive osteogenesis imperfecta - Lei Xi; Shanshan Lv; Hao Zhang; Zhen‐Lin Zhang (Molecular Genetics & Genomic Medicine, 2021)
Abstract Background Osteogenesis imperfecta (OI) is a rare heritable bone disorder that is characterised by increased bone fragility and recurrent fractures. To date, only 19 OI patients have been reported, as caused by BMP1 gene mutations, worldwide. Here, we report a patient with a BMP1 gene mutation to explore the relationship between genotype and phenotype, and the patient was followed up for 4 years. Methods Detailed clinical features were collected, and BMP1 mutational analysis was performed by next‐generation sequencing and Sanger sequencing. Results The patient had recurrent fractures, low bone mass, bone deformities and growth retardation but did not have hearing loss or dentinogenesis imperfecta. Next‐generation sequencing and Sanger sequencing revealed a heterozygous novel missense variant (c.362C>T in exon 3, p.Ala121Val) and a heterozygous novel deletion mutation (c.1252delA in exon 10, p.Ser418AlafsX22). The parents of the proband were heterozygous carriers of these mutations. The patient received regular weekly treatment of 70 mg oral alendronate for 3 years, and her BMD Z‐score for the femur significantly increased from −1.3 to 0.9 at L1‐4 and from −1.7 to −0.1. She had no fracture during 4 years of follow‐up. Conclusion We discovered two heterozygous novel mutations in an OI patient with BMP1 gene mutations, expanding the spectrum of gene mutations in OI.